Ethnic and racial diversity in eating disorder prevention trials. Issue 2 (4th March 2019) - Rodgers, Rachel F.; Donovan, Elizabeth; Cousineau, Tara M.; McGowan, Kayla; Yates, Kayla; Cook, Elizabeth; Lowy, Alice S.; Franko, Debra L.
ABSTRACT: Recruiting diverse samples for prevention trials is challenging, but essential. This paper provides baseline data for four racial/ethnic groups from a randomized controlled trial of a mobile-based prevention intervention and systematically reviews recruitment trends in diversity across technology-based prevention studies. Female emerging adults completed measures of appearance esteem, body image flexibility, appearance comparison, and self-compassion. White participants reported lower body esteem and body image flexibility, and higher appearance comparison compared to Black and Asian participants. Latina participants evidenced higher appearance comparison compared to Black participants. The literature review revealed that while rates of diversity in previous trials vary, the majority of the participants were White. Efforts are needed to increase diversity in prevention trials.